Community enforcement and tenure security: A fuzzy-set qualitative Comparative analysis of twelve community forest management initiatives in the Peruvian Amazon. (January 2023) - van der Zon, Marieke; de Jong, Wil; Arts, Bas
Highlights: Strong community enforcement mechanisms are indispensable for effective forest conservation by local communities. Communities can successfully conserve their forests, even without legal ownership over those forests. Conservation initiatives in communities with strong community enforcement mechanisms are more likely to be successful if they also have access to local government help for sanctioning. Strong leaders, institutions, and rules together facilitate the existence of strong conservation enforcement mechanisms in communities. Conservation initiatives in communities with strong community enforcement mechanisms are more likely to be successful if they also have legal rights to conserve the forest. Abstract: The interest of policymakers in community management of tropical forests is ever growing. Yet, a large research body shows varied levels of success of community conservation initiatives. While policymakers often prioritize legal forest ownership, mostly land titles, consensus exists that success rather depends on a broader set of local institutional arrangements and their fit with the forest context. In this paper, we contribute to building theory on these institutional arrangements and their interaction. We apply a fuzzy set Qualitative Comparative Analysis to case study data on 12 voluntary community conservation initiatives in northern Peru to explore the relationship between local enforcement, legal and alternative property rights, and conservation effectiveness. As recommended for QCA our case selection was intentional and the cases exhibit diverse conservation successes, geographic characteristics, legal and customary property rights, and enforcement mechanisms. We conclude that strong community enforcement mechanisms are indispensable for effective conservation in voluntary initiatives. Furthermore, we find for cases with strong enforcement mechanisms, that some government back-up, i.e., local government support for enforcement and/or legal rights to conserve the forest, significantly increases conservation effectiveness. Strong conservation enforcement tends to be present in communities with strong forest rules, leaders, and pre-existing community institutions. Our findings suggest the importance of paying close attention to community characteristics during project design and refraining from one-size-fits-all-solutions, such as focusing mainly on the presence of legal ownership rights over the forest. Instead, more focus needs to be placed on understanding existing community institutions and supporting communities to strengthen and adapt these for conservation enforcement, rather than imposing new arrangements. Finally, policymakers can help community enforcement institutions become even more effective, by providing them with legal rights to conserve the forest and by strengthening their relationship with local governments so that they receive support in situations they struggle to handle alone.